2005
DOI: 10.1302/0301-620x.87b10.16228
|View full text |Cite
|
Sign up to set email alerts
|

Results of open arthrolysis for the treatment of stiffness after total knee replacement

Abstract: Stiffness is an uncommon but potentially debilitating complication following total knee replacement (TKR). The treatment of this condition remains difficult and controversial. We present the results of 13 patients who underwent open arthrolysis for stiffness. The mean time between TKR and arthrolysis was 14 months. The mean follow-up was 7.2 years (2 to 10). The mean range of movement prior to arthrolysis was 55 degrees . This increased to 91 degrees , six months after arthrolysis (p < 0.005). The improved ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Fourth, we did not confirm arthrofibrosis histologically, as was reported by Parvizi et al [35]. Fifth, some might view complete revision as being overly aggressive compared with lysis of adhesions [17], arthroscopic resection of the posterior cruciate ligament [49], exchange of modular polyethylene [1], and partial revision. This view assumes stiffness is a result of a biologic response to the surgery, rather than some mechanical aspect in surgical technique.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fourth, we did not confirm arthrofibrosis histologically, as was reported by Parvizi et al [35]. Fifth, some might view complete revision as being overly aggressive compared with lysis of adhesions [17], arthroscopic resection of the posterior cruciate ligament [49], exchange of modular polyethylene [1], and partial revision. This view assumes stiffness is a result of a biologic response to the surgery, rather than some mechanical aspect in surgical technique.…”
Section: Discussionmentioning
confidence: 67%
“…This view assumes stiffness is a result of a biologic response to the surgery, rather than some mechanical aspect in surgical technique. Further, there is substantial disagreement among some of these studies; one describes 100% success after open lysis of adhesions in 13 stiff TKAs [17], and another reports 100% failures [1]. This dichotomy might have been resolved by preoperative CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…The mean Knee Society Function score was evaluated in two out of the total five studies [29,30] and was shown to be 83 and 46 respectively at final follow up. The mean Knee Society Knee score was also evaluated in two out of five studies [29,31] and was shown to be 72 and 77 respectively. The mean Knee Society Pain Score was reported in two out of five studies [2,30], at 44 and 39.6 respectively at final follow up.…”
Section: Open Surgical Releasementioning
confidence: 99%
“…Small impairments of ROM of the knee can cause gait disturbances and significantly increase the energy expenditure for daily activity. A knee flexion contracture of as little as 5° may result in a limp, and a permanent knee contracture of greater than 10° may require surgical interventions …”
mentioning
confidence: 99%